The conserved genetic background for pluteus arm development in brittle stars and sea urchin. Issue 2 (15th January 2016) - Morino, Yoshiaki; Koga, Hiroyuki; Wada, Hiroshi
SUMMARY: Echinoderm pluteus larvae are considered a classical example of convergent evolution that occurred in sea urchins and brittle stars. Several genes are known to be involved in the development of pluteus arms in sea urchins, including fgfA, pax2/5/8, pea3, otp, wnt5, and tet . To determine whether the convergent evolution of larval arms also involves these genes in brittle stars, their expression patterns were determined in brittle star. We found that all genes showed similar expression in the arms of ophiopluteus to that seen in echinopluteus, suggesting that convergent evolution of pluteus arms occurred by recruitment of a similar set of genes. This may be explained by our observation that some of these genes are also expressed in the spine rudiment of direct‐type development sea urchins. We propose an evolutionary scenario wherein the pluteus arms of both echinopluteus and ophiopluteus were acquired by independent co‐options of the genetic module responsible for the projection of the adult skeleton.